PS-C01-3: ACCURACY OF THE AKTIIA BRACELET IN THE ELDERLY IN DIFFERENT BODY POSITIONS. (January 2023) - Theiler, Kenji; Sola, Josep; Alexandre, Jeremy; Vermare, Pascale; Durgnat, Virginie; Wuerzner, Gregoire
Abstract : Objective: Accurate blood pressure (BP) measurement is essential for the correct diagnosis and management of hypertension (HTN) especially in the elderly population, which has the highest prevalence of HTN. Recently cuffless devices have been developed with the hope of facilitating blood pressure measurement. However, validation studies of cuffless are scarce and a universally accepted validation protocol has yet to be published. The objective of the second arm of this study (NCT04027777) was to test the accuracy of the Aktiia bracelet in an elderly population cohort in different body positions. Design and method: We recruited 40 patients aged from 65 to 85 years with different blood pressure categories and without diabetes. BP measures from Aktiia Bracelet were compared to reference double auscultatory measurement in various body positions: sitting, standing and lying (including after aerobic physical activity in supine position) on four separate visits distributed over one month. Results: The average participant's age was 73 ± 6 years with 52.5% female participants. A total of 469 comparison measurements were made, with an overall acceptance rate of 79% (percentage of optical recordings with sufficient quality to be analyzed by the cuffless device). Five participants were excluded either due to failed initialization or to ensure a distribution of blood pressure categories compliant to the requirements of ISO 81060-2. After initialization procedures on day 1, we observed means and standard deviations of differences for systolic BP of 1.23 ± 7.88 mmHg in sitting position, -1.81 ± 11.11 mmHg in the standing and -1.8 ± 9.96 mmHg in the lying position (including after aerobic exercise). Differences for diastolic BP were 0.2 ± 5.55 mmHg, -5.35 ± 7.75 mmHg and -0.94 ± 7.47 mmHg respectively. The acceptance rate for each position was 86%, 69% and 75% respectively. When considering all possible body positions representative of a realistic use of the device, and along the entire monitoring period of one month, systolic and diastolic BP differences were -0.26 ± 9.96 mmHg and -0.75 ± 7.0 mmHg respectively. Figure 1 illustrates the Bland-Altman plots for SBP and DBP for the sitting position. Conclusions: This study demonstrates that the Aktiia bracelet can accurately estimate the BP in an elderly population in the sitting position (according to the requirements of ISO 81060-2) and in other body positions representative of a realistic use of the device. The use of more comfortable, non-invasive and non-occlusive BP monitoring may contribute to better diagnosis and treatment of hypertension in the elderly through patient empowerment.